On the Other Hand...: Enhancing Promotional Effectiveness with Haptic Cues - Maille,Virginie; Morrin,Maureen; Reynolds-McIlnay,Ryann (Journal of Marketing Research, 2020)
People like graspable objects more when the objects are located on the dominant-hand side of their body or when the handles point toward their dominant-hand side. However, many products do not have handles or are not graspable (e.g., services, objects hanging on the wall). Can nongraspable products nevertheless benefit from the effects of appealing to viewers’ dominant hands? The present research shows that, yes, consumers respond more positively to nongraspable products if a haptic cue (an object that is graspable or suggestive of hand action) is located within the same visual field as the target and is positioned to appeal to the viewer’s dominant hand. This result is driven by the creation and transfer of perceived ownership from cue to target. These findings extend the use of haptic cues to nongraspable products and uncover the critical role played by perceived ownership, including its ability to transfer from one object to another located in the same visual field. Moreover, the current research demonstrates situations in which the use of haptic cues will not enhance response.
Keywords: Marketing